Analisis Pendapatan dan Kelayakan Usaha Tani Jagung Hibrida (Zea mays L) di Desa Bumi Harjo Kabupaten Kotawaringin Barat - Shofiyah Shofiyah (Anterior Jurnal, 2019)
Bumi Harjo Village, Kumai District is one of the villages that has experienced developments in agriculture. Bumi Harjo Village farmers do hybrid corn farming. The objectives of this study were: to find out the income, and the feasibility of hybrid corn farming in Bumi Harjo Village and to know the prospects for the development of its business. The data analysis method used to determine income and feasibility using the t-test and Pearson correlation formula to determine the level of relationships between variables. The results showed that the average salary received by respondent farmers was 2,089,917/ha, and hybrid maize farming in Bumi Harjo Village was feasible to run with an R/C ratio > 1 which was 7.1. Based on the t-test it was found that the correlation between income and land area obtained t count = 9,346 > t table = 2,052 which means that there is a strong relationship, namely the more significant the land area, the higher the income earned. While the prospect of development is quite good, seen from the increase in the number of livestock populations in 2013 with animal feed needs reaching 2,183 tons per month, thus hybrid corn farming can be a recommendation for sustainable business.